Chromosome spreading of associated transposable elements and ribosomal DNA in the fish Erythrinus erythrinus. Implications for genome change and karyoevolution in fish - Cioffi, Marcelo B.; Martins, Cesar [UNESP]; Bertollo, Luiz A. C. (Biomed Central Ltd., 2010)
Background: The fish, Erythrinus erythrinus, shows an interpopulation diversity, with four karyomorphs differing by chromosomal number, chromosomal morphology and heteromorphic sex chromosomes. Karyomorph A has a diploid number of 2n = 54 and does not have differentiated sex chromosomes. Karyomorph D has 2n = 52 chromosomes in females and 2n = 51 in males, and it is most likely derived from karyomorph A by the differentiation of a multiple X(1)X(2)Y sex chromosome system. In this study, we analyzed karyomorphs A and D by means of cytogenetic approaches to evaluate their evolutionary relationship.Results: Conspicuous differences in the distribution of the 5S rDNA and Rex3 non-LTR retrotransposon were found between the two karyomorphs, while no changes in the heterochromatin and 18S rDNA patterns were found between them. Rex3 was interstitially dispersed in most chromosomes. It had a compartmentalized distribution in the centromeric regions of only two acrocentric chromosomes in karyomorph A. In comparison, in karyomorph D, Rex3 was found in 22 acrocentric chromosomes in females and 21 in males. All 5S rDNA sites co-localized with Rex3, suggesting that these are associated in the genome. In addition, the origin of the large metacentric Y chromosome in karyomorph D by centric fusion was highlighted by the presence of internal telomeric sites and 5S rDNA/Rex3 sites on this chromosome.Conclusion: We demonstrated that some repetitive DNAs (5S rDNA, Rex3 retroelement and (TTAGGG)(n) telomeric repeats) were crucial for the evolutionary divergence inside E. erythrinus. These elements were strongly associated with the karyomorphic evolution of this species. Our results indicate that chromosomal rearrangements and genomic modifications were significant events during the course of evolution of this fish. We detected centric fusions that were associated with the differentiation of the multiple sex chromosomes in karyomorph D, as well as a surprising increase of associated 5S rDNA/Rex3 loci, in contrast to karyomorph A. In this sense, E. erythrinus emerges as an excellent model system for better understanding the evolutionary mechanisms underlying the huge genome diversity in fish. This organism can also contribute to understanding vertebrate genome evolution as a whole.